O Zastosowaniu Zasady Hamiltona do Wyprowadzania Równań Drgań Giętnych Belki z Uwzględnieniem Ścinania - Stojek, Z. (Engineering Transactions, 1960)
The paper deals with derivation by means of the HAMILTON principle of the differential equations of free bending vibrations of a beam in the general case (taking into account the influence of shears). The result is a system of two differential equations (21) for eigenfunctions. As an illustration the system (21) is solved by the GALERKIN method.